Co-existence of two freshwater copepods in lakes through size divergence and diet partitioning. - Chow-fraser P; Maly EJ (NRC Research Press, 2025)
We examined the vertical and horizontal distribution patterns of Diaptomus minutus Lilljeborg and Diaptomus oregonensis Forbes in several shallow Quebec lakes where they occurred allopatrically and sympatrically within a small geographic region. Both species overlapped extensively in their vertical and temporal distributions and were found to be positively associated within and among lakes. Although size displacement coul dnot b e detected when body lengths of sympatric and allopatric populations were compared, in lakes where the was a reduction in size overlap between species, the two species co-existed at relatively high densities. This contrasted with situations where convergence in size between species was accompanied by a limited abundance of one or both diaptomids. We conducted stomach-content analyses on the sympatric populations of two of these lakes to determine if diet preference was related to copepod size divergence, an dif algae were selected as a function of copepod size. We found that D. minutus, the smaller copepod, preferentially digested a number of small algal particles (< 10 µm) whereas D. oregonensis, the larger copepod, tended to ingest a greater number of larger particles. Although preference for small algae (Selenastrum and small blue-green algae) was negatiavely correlated with prosome length, preference for larger algal taxa (Planktosphaerium, centric diatoms such as Melosira, and Achnanthes) was positively correlated with diaptomid size. There were, however, differences with respect to the degree of diet overlap between species in the two lakes, which was reflected in a significant negative correlation between dietary and size overlap. These observations are consistent with the hypothesis that reduction in size overlap has resulted in reduced exploitative competition, and that divergence in size and diet may be the mechanism that allows D. minutus and D. oregonensis to co-exist when food becomes limited.